2012
DOI: 10.1159/000341482
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Ski in Fibroblast is Implicated in the Peroxisome Proliferator- Activated Receptor d-Mediated Wound Healing

Abstract: Background/Aim: Both peroxisome proliferator-activated receptor (PPAR) δ and Ski are investigate the interaction of PPARδ and Ski and this interaction-associated effect in wound healing. Methods: Effect of PPARδ activation on Ski expression was detected in rat skin fibroblasts by real-time PCR and western blot. Luciferase assay, electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP) assay were performed to identify the binding site of PPARδ in the promoter region of rat Ski gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
2
9
0
1
Order By: Relevance
“…It has reported that upregulation of Ski to promote fibroblast proliferation is implicated in wound healing (Li et al, 2012). And, increasing Ski protein level is capable of accelerating wound healing (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has reported that upregulation of Ski to promote fibroblast proliferation is implicated in wound healing (Li et al, 2012). And, increasing Ski protein level is capable of accelerating wound healing (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As a versatile transcriptional regulator, it modulates the expression of multiple genes and is involved in many physiological and pathological processes [5]. Our previous studies confirmed the following: increased c-Ski expression at low TGF-β1 concentrations (from 2.5 pg/ml to 250 pg/ml) promotes fibroblast proliferation; reduced c-Ski expression at high TGF-β1 concentrations (> 2.5 ng/ml) inhibits proliferation [5]; and c-Ski achieves the optimal repair effect by promoting wound repair and inhibiting scar formation, but increased c-Ski expression has no significant effect on cell transformation induced by TGF-β1 [9][10][11][12]. High TGF-β1 concentrations negatively regulate c-Ski expression levels by inducing c-Ski degradation through the Smad2/ 3 signaling pathway [13,14], but the mechanism by which low TGF-β1 concentrations regulate c-Ski levels remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…c-Ski, a homologue of v-Ski in cells, is a versatile transcriptional regulator that is widely distributed in different cells, such as skeleton muscle cells, tumor cells, fibroblasts and VSMCs [13][17]. Previously, we have found it can suppress VSMC proliferation stimulated by transforming growth factor β (TGF-β) [18].…”
Section: Introductionmentioning
confidence: 99%